The Inscriptions on the Tillya-tepe and Pushkalavati Coins: Epigraphic, Linguistic, and Literary Remarks - Baums, Stefan ca. 20./21. Jh. (JAOS, 2023)
This article discusses paleographic and linguistic aspects of the Kharoṣṭhī inscriptions on the Tillya-tepe and Pushkalavati coins and adduces some epigraphic and literary parallels. It proposes a syntactically separate reading of the two sides of the Tillya-tepe coin, and concludes that in spite of some differences of execution the coins may have been produced in the same workshop.